Analisis Customer Experince, Brand Image, dan Religiousity dalam Mempengaruhi Customer Loyalty (Studi pada Produk Boikot Pro Israel) - Hamidah Tussifah; Nur Choirina Ma’rufah; Nawa Marjany (Journal of Innovative and Creativity, 2025)
The article titled "Analysis of Customer Experience, Brand Image, and Religiosity in Influencing Customer Loyalty (Study on Boycotted Pro-Israel Products)" is a scientific paper aimed at building research hypotheses on the influence between variables that can be used in future studies within the scope of marketing management. The research method used is a library research method, sourcing from online media such as Google Scholar, Mendeley, and other academic platforms. The findings of this study reveal that, despite the widespread boycott of pro-Israel products, customer experience influences customer loyalty. Brand image positively influences customer loyalty in some places and vice versa. Some studies show that religiosity has a negative impact on loyalty, while others show that religiosity positively affects customer loyalty due to a good brand image.